Personnel administration : a guide to effective management of human resources - Ream, Betty (ICSA Publishing CambridgeGB, 1984)
Discusses company and administrative law as it relates to administrative procedures. Gives guidance on the assessment of manpower requirements, staff selection and recruitment, interview techniques, training and employee benefits. Discusses the legal requirements relating to conditions of employment, keeping of personnel records as well as the technical aspects of wages, salaries and pensions administration. Considers the relationship between individual effort and organizational effectiveness and the implications for training and career development. Discusses industrial relations including dispute and disciplinary procedures, collective bargaining and termination of employment. Lists relevant legislation, and codes of practice.